Relative effectiveness of preceding and succeeding morphological cues in category learning by 2-year old children - Tropé, Anaïs (The University of Edinburgh, 2013)
Research on the differential role of preceding and succeeding morphological cues in category learning by adults has uncovered a suffixing preference. The present study investigated whether 2-year-old children also benefited more from suffixes when learning word categories than from prefixes. Using the looking-while-listening procedure, children were taught an artificial language containing two word categories, animate and inanimate. These categories could be reliably distinguished by either a preceding morphological cue (i.e, prefix condition) or a succeeding morphological cue (i.e., suffix condition). In the familiarisation phase, participants saw single pictures of three animate and three inanimate items and heard the correspondent labelling two times. The participants’ ability to use the marker element to categorise words was tested by presented the children with both a pair of items seen in the familiarisation phase (i.e., familiar test trials) and a pair of novel item (i.e., generalisation test trials). The proportion of looking time to the target object was then used as a measure to investigate which of the morphological cues facilitated learning. The results of the experiment did not significantly show that children were biased to use the succeeding marker element over the preceding one, even though this was the trend. Issues with the experiment design and the statistical analysis are considered as possible explanations. Although this study is not conclusive, it appears that children behave like adult learners in category assignment task, at least when presented with a systematic language.
The relative effectiveness of preceding and succeeding morphological cues in category learning by 2-year old children
Keywords: morphology; category learning